A Simulation Study On Kanban Control Systems - Mirbirjandian, Ehsan (2011)
The main purpose of this paper is to compare three kinds of different pull control systems namely Kanban Control System (KCS), Constant Work-in-Process (CONWIP) and Base-Stock Control System (BSCS) in two kinds of essentially different production lines, using the Witness simulation software. Simulation studies were performed to evaluate the performance measures like average machine utilization, average work-in-process (WIP) and average WIP holding time in these production lines when each of them was run with the optimized number of Kanbans. In other words, the three pull control systems were compared in their optimum situation. According to the results, CONWIP has the fewest average WIP and average WIP holding time as compared to the other systems. In terms of average machine utilization, all the three production control systems behaved almost the same. Overall, it can be said that CONWIP outperformed BSCS and KCS, and BSCS showed the worst performance in the above criteria.